2019
DOI: 10.1093/ajcn/nqy284
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality in a nationally representative sample of American children by sociodemographic characteristics

Abstract: Background To date, Healthy Eating Index 2015 (HEI-2015) scores have not been published in the peer-reviewed literature for nationally representative samples of American children. Objective The aim of this study was to use the HEI-2015 to describe the diet quality of American children overall and within various sociodemographic populations. Design We used 3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
88
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 12 publications
13
88
2
Order By: Relevance
“…This study assessed adolescent diet quality utilizing HEI-2010, as well as analyzing trends over time [33]. Consistent with other analyses [33,[39][40][41][42], overall diet quality was shown to decrease with age as adolescents persistently had significantly lower overall HEI scores compared to younger youth [33]. Furthermore, results indicated that adolescents 12-18 years had an average overall HEI score of 48.4 out of 100 in the 2011-2012 NAHNES cycle, which was a significant increase from the average overall score of 40.4 observed during the 1999-2000 cycle [33].…”
Section: Diet Qualitysupporting
confidence: 58%
See 4 more Smart Citations
“…This study assessed adolescent diet quality utilizing HEI-2010, as well as analyzing trends over time [33]. Consistent with other analyses [33,[39][40][41][42], overall diet quality was shown to decrease with age as adolescents persistently had significantly lower overall HEI scores compared to younger youth [33]. Furthermore, results indicated that adolescents 12-18 years had an average overall HEI score of 48.4 out of 100 in the 2011-2012 NAHNES cycle, which was a significant increase from the average overall score of 40.4 observed during the 1999-2000 cycle [33].…”
Section: Diet Qualitysupporting
confidence: 58%
“…Furthermore, results indicated that adolescents 12-18 years had an average overall HEI score of 48.4 out of 100 in the 2011-2012 NAHNES cycle, which was a significant increase from the average overall score of 40.4 observed during the 1999-2000 cycle [33]. On trend with overall diet quality improving over time [33], the overall HEI-2015 score for adolescents 12-18 years was 52.0 in a more recent analysis [42]. Although overall diet quality scores have significantly improved over time for adolescents, the current scores are still considered low [33,42].…”
Section: Diet Qualitymentioning
confidence: 84%
See 3 more Smart Citations